Thalassia testudinum as a potential vector for incorporating microplastics into benthic marine food webs. (October 2018) - Goss, Hayley; Jaskiel, Jacob; Rotjan, Randi
Abstract: Seagrasses are among the most productive shallow water ecosystems, serving a diverse assemblage of fish and invertebrates. Tropical seagrass communities are dominated by the turtle grass Thalassia testudinum, whose wide, flattened blades host diverse epibiont communities. Amidst its epibionts, T . testudinum may also be accumulating microplastics, which are a ubiquitous marine pollutant even in remote locales. To assess the extent of microplastic accumulation, seagrass samples were collected from Turneffe Atoll, which lies offshore but parallel with a major urban center. Seventy-five percent of Thalassia blades had encrusted microplastics, with microfibers occurring more than microbeads and chips by a ratio of 59:14. Grazers consumed seagrasses with higher densities of epibionts. Potential mechanisms for microplastic accumulation include entrapment by epibionts, or attachment via biofilms. This study is the first to document microplastics on marine vascular plants, suggesting that macroherbivory is a viable pathway for microplastic pollution to enter marine food webs. Highlights: Microplastics were found on the tropical seagrass, Thalassia testudinum . Seagrass microplastics are encrusted by epibionts. 75% of seagrass blades examined had at least one microplastic particle. Herbivorous fishes in seagrass ecosystems eat blades with high densities of epibionts. Herbivory is a viable pathway for microplastic pollution to enter marine food webs.